Can the interRAI home care instrument be applied to the definition criteria of the Global Leadership Initiative on Malnutrition (GLIM)? A longitudinal study. Issue 11 (November 2020) - de Almeida Mello, Johanna; Fávaro-Moreira, Nádia Cristina; Krausch-Hofmann, Stefanie; Vanneste, Dirk; Matthys, Christophe; Declercq, Anja; Duyck, Joke
Summary: Background & aims: As malnutrition is an important modifiable risk factor for poor clinical outcomes, it is important to target malnourished older people and older people at risk of malnourishment. The Global Leadership Initiative on Malnutrition (GLIM) recently reached a consensus for a global definition of malnutrition. The primary aim of this study was to apply the interRAI Home Care (interRAI HC) instrument to fit the GLIM definition criteria of malnutrition to the closest. A second goal was to identify potential risk factors associated with malnutrition using this comprehensive assessment and to quantify their association. Methods: This is a case control study, which retrospectively determines the exposure to the risk of malnutrition and estimates its potential risk factors. The longitudinal data came from a larger study called Protocol 3. Eligibility criteria were a minimum age of 65 years old, a minimum score of 6 on the Edmonton Frail Scale or at least a moderate level of functional impairment measured by a Belgian version of the Katz scale. Older people with an official dementia diagnosis were also eligible. Bivariate analysis was performed and logistic regression models were developed in order to identify significant determinants of malnutrition. Results: The data consisted of 6334 frail older people (mean age: 80.6 ± 6.9, 70.6% female). About 2.4% became malnourished within a follow-up period of one year after baseline. The adjusted logistic regression yielded significant odds ratios for dysphagia (OR 2.2), loss of appetite (OR 1.8), bladder incontinence (OR 1.5) and low fluid intake (OR 1.5). Diabetes (OR 0.5) and visits to the physician (OR 0.5) had both a significant reverse effect. Conclusions: This study was the first large longitudinal research to explore the risk factors of malnutrition with a comprehensive assessment instrument as the interRAI HC, applying it to the recent GLIM definition criteria. The worldwide use of the interRAI instruments makes these findings relevant for global clinical practice and research. Adapting the interRAI instruments to the GLIM definition improves accurate detection, prevention and early treatment of malnourishment, avoiding further health deterioration in older people. Graphical abstract: Image 1